The impact of primary colorectal cancer treatment on physical symptoms and functioning in the first two years: results from the colorectal well-being (CREW) cohort study - Foster, Claire; Haviland, Joanne; Winter, Jane; Grimmett, Chloe; Chivers Seymour, Kim; Calman, Lynn; Corner, Jessica; Din, Amy; Fenlon, Deborah; May, Christine M.; Smith, Peter W.; Richardson, Alison (Wiley, 2016)
Abstract of the presentation at the British Psychosocial Oncology Society 2016 Annual Conference, 3–4 March 2016, Cambridge, UK.